Hubungan Pemberian ASI Dengan Kejadian Pneumonia Pada Balita Usia 7-24 Bulan Di Wilayah Kerja Puskesmas Metro Utara - Sumiyati, Sumiyati (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2016)
Incidence pneumonia in babies in health center of north metro of 25 % , this number is higher than the level targeted by the program buster disease tract ( pneumonia ) set rate of 10 % toddlers as a target discovery patients pneumonia toddlers in a territory. The provision of breastfeeding not exclusively cause of occurrence of pneumonia. Research aims to understand relations the provision of breastfeeding not exclusively in toddlers age 7-24 months in the work area health center of north metroÂ 2015. The kind of research this quantitative, design analytic with the approach case control. Population cases namely all toddlers age 7-24 months suffering from pneumonia and treatment at health center of north metro 2015 at 38 toddlers. Sample control that all toddlers age 7-24 months treatment at health center of north metro 2015 at 38 toddlers. Sample cases at 38 toddlers sample control of 38 toddlers taken to technique consecutive sampling by comparison 1:1. Way data collection with the questionnaire. The independent variable subjects the provision of breastfeeding not exclusively, dependent variable pneumonia. Analysis using by test chi square. The result of univariat test shows the proportion of the provision of breastfeeding not exclusively as many as 52.6 % ( 40 ). The results of statistical tests chisquare about the relationship breastfeeding not exclusively with pneumonia in toddlers age 7-24 months the results value = 0,003 which would mean there are meaningful relations between breastfeeding not exclusively with the genesis pneumonia in toddlers age 7-24 months. Conclusion research is the connection the provision of breastfeeding not exclusively with the genesis pneumonia in toddlers age 7-24 months. Angka kejadian pneumonia pada balita di Puskesmas Metro utara sebesar 25%, angka ini lebih tinggi dari angka yang ditargetkan oleh Program Pemberantas Penyakit ISPA (Pneumonia) menetapkan angka 10 % balita sebagai target penemuan penderita pneumonia balita pada suatu wilayah. Pemberian ASI tidak Eksklusif penyebab dari kejadian pneumonia. Penelitian ini bertujuan untuk mengetahui hubungan pemberian ASI tidak Eksklusif pada balita usia 7-24 bulan di wilayah kerja Puskesmas Metro Utara Tahun 2015. Jenis penelitian ini kuantitatif, rancangan analitik dengan pendekatan case control. Sampel kasus yaitu semua balita usia 7-24 bulan yang menderita pneumonia dan berobat di Puskesmas Metro Utara tahun 2015 sebesar 38 balita. Sampel kontrol yaitu semua balita usia 7-24 bulan yang berobat di Puskesmas Metro Utara tahun 2015 sebesar 38 balita. Sampel kasus sebesar 38 balita dan sampel kontrol sebesar 38 balita diambil dengan teknik Consecutive sampling dengan perbandingan 1:1. Cara pengumpulan data dengan kuesioner. Variabel independen yang diteliti pemberian ASI tidak Eksklusif, variabel dependen pneumonia. Analisis menggunakan dengan uji chi square. Hasil uji univariat menunjukkan proporsi pemberian ASI tidak Eksklusif sebanyak 52,6% (40). Hasil uji statistik chi square tentang hubungan ASI tidak Eksklusif dengan pneumonia pada balita usia 7-24 bulan diperoleh hasil p value=0,003<a(0,05) yang berarti ada hubungan yang bermakna antara ASI tidak Eksklusif dengan kejadian pneumonia pada balita usia 7-24 bulan. Kesimpulan penelitian ini yaitu adanya hubungan pemberian ASI tidak Eksklusif dengan kejadian pneumonia pada balita usia 7-24 bulan.